Effect of quality of recycled aggregates on bond strength between concrete and embedded steel reinforcement. Issue 2 (3rd March 2020) - Assaad, Joseph J.; Matar, Pierre; Gergess, Antoine
Abstract : The use of recycled concrete aggregate (RCA) in structural applications considerably increased. The main objective of this paper is to assess the effect of parent concrete (PC) quality on RCA properties including concrete durability and bond to steel reinforcement. Four RCA types are considered; three were sourced from 13, 42, and 62-MPa compressive strength ( f 'c ) normal-density PC, while the fourth type was derived from lightweight PC. Test results showed that the PC quality has direct influence on the transfer of stresses and ultimate bond strengths to embedded rebars. The incorporation of styrene-butadiene rubber (SBR) latexes was found efficient to mitigate the drop in concrete mechanical properties including f 'c, splitting tensile strength, electrical resistivity, and ultimate bond strength to embedded steel. The experimental data are compared to the design bond strengths specified in international codes such as ACI 318-17, European Code EC-2, and fib Model Code MC2010.